1992
DOI: 10.1126/science.1470917
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of a Live Attenuated SIV Vaccine with a Deletion in the nef Gene

Abstract: Vaccine protection against the human immunodeficiency virus (HIV) and the related simian immunodeficiency virus (SIV) in animal models is proving to be a difficult task. The difficulty is due in large part to the persistent, unrelenting nature of HIV and SIV infection once infection is initiated. SIV with a constructed deletion in the auxiliary gene nef replicates poorly in rhesus monkeys and appears to be nonpathogenic in this normally susceptible host. Rhesus monkeys vaccinated with live SIV deleted in nef w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
597
1
7

Year Published

1994
1994
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 996 publications
(626 citation statements)
references
References 19 publications
19
597
1
7
Order By: Relevance
“…Live attenuated SIV vaccines can confer effective protection against detectable superinfection with pathogenic, wild-type SIV (3,13,14,29,58,59) and SIV/HIV-1 chimeric virus (7,18,46). Yet there are limits to the breadth of this protection, and live attenuated SIV vaccines have failed to protect against certain heterologous challenge viruses or failed to protect against a challenge performed several years postinoculation (22,31,58).…”
mentioning
confidence: 99%
“…Live attenuated SIV vaccines can confer effective protection against detectable superinfection with pathogenic, wild-type SIV (3,13,14,29,58,59) and SIV/HIV-1 chimeric virus (7,18,46). Yet there are limits to the breadth of this protection, and live attenuated SIV vaccines have failed to protect against certain heterologous challenge viruses or failed to protect against a challenge performed several years postinoculation (22,31,58).…”
mentioning
confidence: 99%
“…Because of the safety concerns and inadequate protection of the more attenuated liveattenuated vaccine, the vaccine field is currently not actively pursuing live-attenuated vaccines for use in humans. 1,4,6,[27][28][29][30] Previously, the efficacy of various Adand MVA-based vaccines about the susceptibility to SHIV infection in monkeys has been examined by our research group and other scientists. 10,24 This study investigates whether a combination of these vaccines can prevent SIV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Vaccination of rhesus monkeys with live-attenuated simian immunodeficiency virus (SIV) vaccine was shown to provide protective immunity against disease after challenge with pathogenic SIV. [1][2][3][4] However, the live-attenuated SIV/HIV possesses the potential risk of the vaccine virus reverting to a pathogenic form. Indeed, a study in which 11 adult monkeys were vaccinated with SIVmac239Delta3 reported that in the 6.8-year period after vaccination, all the monkeys had signs of immune dysregulation, 64% of the monkeys had persistent recurrent viremia, and 18% of the monkeys developed AIDS.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies, however, demonstrated that Nef plays an important role in several steps of HIV replication. In addition, it appears to be a critical pathogenic factor, as Nef-deficient SIV and HIV are significantly less pathogenic than the wild-type viruses [95][96][97], whereas Neftransgenic mice show many features characteristic to HIV disease [98,99].…”
Section: Negative Regulator Factor(nef)mentioning
confidence: 99%